2022
DOI: 10.1038/s41467-022-28332-6
|View full text |Cite
|
Sign up to set email alerts
|

A diencephalic circuit in rats for opioid analgesia but not positive reinforcement

Abstract: Mu opioid receptor (MOR) agonists are potent analgesics, but also cause sedation, respiratory depression, and addiction risk. The epithalamic lateral habenula (LHb) signals aversive states including pain, and here we found that it is a potent site for MOR-agonist analgesia-like responses in rats. Importantly, LHb MOR activation is not reinforcing in the absence of noxious input. The LHb receives excitatory inputs from multiple sites including the ventral tegmental area, lateral hypothalamus, entopeduncular nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…If both glutamate inputs and GABA inputs are excited by aversive stimuli, and thus compete each other to shape dopamine responses, the dopamine responses to aversive stimuli may be flexibly altered by slight modulations in the relative strength of excitatory and inhibitory inputs, depending on an animal’s state or context (Figure 7G). We focus here on one state alteration: the exogenous administration of opioids, common and effective analgesics which lead to an increase in dopamine excitability and inhibit some direct and indirect inputs to dopamine neurons 4754 . We tested the effect of systemic administration of buprenorphine, an opioid commonly used in medical practice, on dopamine release and glutamate inputs with simultaneous recording (Figure 8; Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…If both glutamate inputs and GABA inputs are excited by aversive stimuli, and thus compete each other to shape dopamine responses, the dopamine responses to aversive stimuli may be flexibly altered by slight modulations in the relative strength of excitatory and inhibitory inputs, depending on an animal’s state or context (Figure 7G). We focus here on one state alteration: the exogenous administration of opioids, common and effective analgesics which lead to an increase in dopamine excitability and inhibit some direct and indirect inputs to dopamine neurons 4754 . We tested the effect of systemic administration of buprenorphine, an opioid commonly used in medical practice, on dopamine release and glutamate inputs with simultaneous recording (Figure 8; Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…In naive animals, activation of μopioid receptors decreased neuronal activity in the lateral habenula via postsynaptic hyperpolarisation and presynaptic inhibition of glutamate release [18]. Microinjection of μ-opioid receptor agonists herein increased paw withdrawal thresholds after nerve injury and produced conditioned place preference, an indirect readout of a positive affective state [19]. As the former represents a spinally mediated sensorimotor response, it would suggest that the actions of opioid receptor agonists within the lateral habenula are at least partly through subsequent engagement of the descending pain modulatory system.…”
Section: Key Pointsmentioning
confidence: 98%
“…Dependent on the precise aetiology and time-dependent plasticity, the locus coeruleus can switch from ‘pain inhibitor’ to ‘pain generator’. Within the descending pathways, chemogenetic silencing of a locus coeruleus to dorsal reticular nucleus projection was antinociceptive in a model of neuropathic pain 22 mediated via α 1 -adrenoreptors in the dorsal reticular nucleus 23 . As further evidence for the existence of parallel and functionally discrete noradrenergic pathways, optogenetic activation of the coeruleospinal module abolished the expression of diffuse noxious inhibitory controls (DNIC) 24 .…”
Section: Neural Circuits For Pain and Affective Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…After selective excitation of MOR, whole-cell patch-clamp recordings in rats showed inhibition of LHb neurons via postsynaptic hyperpolarization and presynaptic inhibition of glutamate release ( 168 ). From a functional perspective, the latest study indicated that nociceptive stimuli activated the LPO projection to the LHb, producing hyperalgesia and related aversive emotions, which negative emotions can be strongly inhibited by specific activation of the LHb MOR, leading to the mitigation of the above symptoms ( 169 ). This showed that the LHb MOR function improves negative emotional experiences in persistent neuropathic pain.…”
Section: Changes In Lateral Habenula Synaptic Transmission During The...mentioning
confidence: 99%